Kontruksi Media Dalam Gerakan Islam Populis 212 - M. Mujibuddin SM (Jurnal Sosiologi Agama, 2018)
This paper studied the movement of Aksi Bela Islam (ABI) which was propagated by the GNPF MUI group to bring down Basuki Tjahaja Purnama from the governor position. This demonstration not only in Jakarta but also the various cities in Indonesia. The involvement of Muslims are influenced by social media. Social media has succeeded in becoming a public sphere for society. Today, society can take a truth from social media. Therefore,  social construction is not only formed from individuals or society but also social media. This research uses literature study with analytical descriptive writing method. This paper uses framing analysis approach and Islam populist. The results of this paper show that social media has an important role in the construction of public awareness. This social construction can be seen with the birth of Islam populist movement 212 which has a goal to reform the bureaucracy in government.Keyword: Social Contruction, Islam Populist, Aksi Bela Islam, Social Media, Post-Truth.